PENANGKAPAN BENIH BETUTU (Oxyeleotris marmorata (Bleeker) DENGAN PANGILAR (Fish Trap) MENGGUNAKAN UMPAN HIDUP - Iriansyah Iriansyah (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
This study aims to determine a suitable tool to capture betutu seed seedling salive and healthy.The results showed that the amount of the catch pangilar (tail) and weight (g) there are differences in catches between treatment A and B by 7 tails and 1050 grams. The total amount of the catch Pangilar (Fish Trap) whether using live bait andlive bait are not using tail is 75 or weighing 5350 grams (5.350 kg) to 16 times there trieval of data by using 30 pieces of gear.